IMPLEMENTASI PROFIT AND LOSS SHARING (PLS) PETANI BAWANG MERAH DITINJAU DARI KONSEP EKONOMI ISLAM - Khasanah, Umrotul (Fakultas Ekonomi, UIN Maliki Malang, 2009)
The purposes of this research are to determine profit and loss sharing form that was used by red onion farmer and to explain itâ€™s implementation according to Islamic concept. Research techniques include study approach, determination of research location, field data collection, and data analysis. Data was classified, identified, generalized, and than searched for theoretical constructions. The result of this research shows that red onion farmer did not know the term of profit and loss sharing well because they usually use â€œpertelonanâ€ term. Implementation of pertelonan is dividing profit into three parts i.e. two parts for the owner of the land and one part for workers of the land. Based on syariâ€™ah concept, this implementation is already according to Islamic law but it is not perfect yet because all process are unwritten or undocumented so if something wrong happened they have not written evidence.